Exposure Dose of Bacteria and Fungi in a Public Primary School in Beni Suef, Upper Egypt - Mostafa, Dr. Mona (JOURNAL OF ADVANCES IN BIOLOGY, 2019)
Potential health risk due to the exposure of bacteria and fungi is mainly related to the concentration of respirable airborne bacteria and fungi in indoor environments. Schools buildings represent an important category of indoor environments. This study aimed to evaluate the concentration and size distribution of bacteria and fungi in classrooms of a public primary school in Beni Suef, Egypt. In addition, the indoor exposure dose (IED) of bacteria and fungi were estimated for children and teachers. A six-stage Andersen impactor was used for collecting the bacterial and fungal particles. Indoor average concentration of bacteria was 1120±458 CFU/m3 while the corresponding fungal concentration was 291±89 CFU/m3. Bacterial level is almost twice the World Health Organization guideline value of 500 CFU/m3 while the fungal level is underestimated. Respirable fraction (<5 µm), that can reach to the lower airways of the lung, of bacteria was 79% while the corresponding respirable fraction of fungi was 90% of the total concentration. The size distribution of bacteria was bimodal in nature and the fungal size distribution was unimodal with lower dispersion than bacteria. IED of bacteria was 211 CFU/kg and 70 CFU/kg for children and teachers, respectively. While the fungal IED was 55 CFU/kg and 18.2 CFU/kg for children and teachers, respectively.